(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2022)
Magnetic iron oxide (Fe3O4) in nano form has been synthesized by a simple wet chemical method involving co-precipitation using iron salt and ammonium hydroxide as precipitating agents. Characterization of the synthesized nanoparticles were carried out by using XRD, FTIR, FESEM and VSM techniques. Crystallite sizes determined from XRD data were found to be between 6.8 and 12.6 nm with face center cubic crystal structures. The lattice parameter was determined to be 8.34 Å. FESEM microstructure revealed a spherical like nanoparticles with average particle size of. The saturation magnetization of the synthesized magnetite nanoparticles was measured to be 49.88 emu/gm. The Fe3O4 nanoparticles synthesized by co-precipitation method is considered to be potentiality good magnetic material with diverse applications. Bangladesh J. Sci. Ind. Res. 57(2), 67-76, 2022